P807 Burden of disease in patients with Crohn's disease: retrospective analysis of cross-sectional survey data from the USA and Germany. (25th January 2019) - Bracher, M; Gorsh, B; Symons, J M; Chauhan, D; Hoskin, B; Lucas, J; Kershaw, J; Middleton, C
Abstract: Background: Individuals with Crohn's disease (CD) experience a wide range of debilitating symptoms covering bowel, abdominal and systemic manifestations 1 with a significant impact on health-related quality of life (HRQoL). This study utilised data from the Adelphi Disease-specific Programme (DSP), a large, cross-sectional survey, to describe the burden of CD in a real-world clinical setting in both the USA and Germany. 2 Methods: This study is a retrospective, descriptive analysis of Adelphi DSP data collected from patients consulting for routine care in the USA and Germany (DE) during Q4 2017 (GSK sponsored analysis; study HO-18-19282). As part of the survey, physicians and patients reported the symptoms currently experienced by the patient. Measures of HRQoL included the short-form Inflammatory Bowel Disease Questionnaire (SIBDQ). Current and prior treatment use was captured. Data were evaluated for the overall population and separately for patients with physician-perceived mild or moderate to severe disease. Results: The total number of participating physicians was 100 (US)/60 (DE), with physician-reported data for 803 (USA)/480 (DE) patients. 328 (USA)/350 (DE) patients provided voluntary patient-reported data. In the overall sample, patients had a mean disease duration since diagnosis of 4.1 (USA)/2.9 (DE) years. At the time of the survey, 52% (USA)/73% (DE) were biologic naïve and 44% (USA)/26% (DE) receiving biologic treatment. Approximately half (50% USA; 55% DE) of the patients were perceived by their physicians to have mild disease, and the remaining moderate or severe. The most common current symptoms were abdominal cramps/pain, non-bloody diarrhoea, rectal urgency and fatigue (Table 1). Notably, physicians reported fatigue severity to be at least moderate in almost a third of mild patients and over three quarters of moderate/severe patients, with similar findings for pain severity. SIBDQ data indicate that QoL was impaired in the overall sample with greatest impairment in the moderate/severe group (Table 1). Conclusions: The symptom burden of CD is high, commonly including bowel, abdominal and systemic symptoms (e.g. fatigue); HRQoL is also impaired. These findings highlight the need for more effective treatments for patients with Crohn's disease. References 1. Higgins PD. Development and validation of the Crohn's disease patient-reported outcomes signs and symptoms (CD-PRO/SS) diary. J Patient Rep Outcomes 2018;2:24. 2. Anderson P, Benford M, Harris N. Real-world physician and patient behaviour across countries: Disease-Specific Programmes - a means to understand. Curr Med Res Opin 2008;24:3063–72.